2021
DOI: 10.1038/s41592-021-01330-0
|View full text |Cite
|
Sign up to set email alerts
|

FlyWire: online community for whole-brain connectomics

Abstract: Due to advances in automated image acquisition and analysis, whole-brain connectomes with 100,000 or more neurons are on the horizon. Proofreading of whole-brain automated reconstructions will require many person-years of effort, due to the huge volumes of data involved. Here we present FlyWire, an online community for proofreading neural circuits in a Drosophila melanogaster brain, and explain how its computational and social structures are organized to scale up to whole-brain connectom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
252
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(253 citation statements)
references
References 55 publications
1
252
0
Order By: Relevance
“…A brain circuit that can select antenna grooming (head sweeps) over front leg rubbing While neurons in the VNC may be capable of enforcing action selection among grooming movements, anatomical evidence indicates that circuits in the brain may also be involved. We identified the DNg11 DNs in the electron microscopy (EM) datasets covering the Drosophila brain using the FlyWire interface 24,25 (Figure 3A) See also Figures S1 and S2.…”
Section: Ll Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…A brain circuit that can select antenna grooming (head sweeps) over front leg rubbing While neurons in the VNC may be capable of enforcing action selection among grooming movements, anatomical evidence indicates that circuits in the brain may also be involved. We identified the DNg11 DNs in the electron microscopy (EM) datasets covering the Drosophila brain using the FlyWire interface 24,25 (Figure 3A) See also Figures S1 and S2.…”
Section: Ll Open Accessmentioning
confidence: 99%
“…In addition, we found that the brain may also play a role. Using the FlyWire platform to reconstruct neurons in a whole-brain electron microscope volume, 24,25 we identified a novel inhibitory circuit connecting head sensory neurons to DNg11s that command front leg rubbing. Different types of sensory neurons may contribute to the selection of appropriate motor subroutines, indicating that decisions between actions can also be made in the brain.…”
Section: Introductionmentioning
confidence: 99%
“… 57 We identified fragment #5813046185 as an excellent match to MooSEZ neurites located within the FlyEM hemibrain volume. Furthermore, using FlyWire, 58 we identified the complete anatomical structure of MooSEZ with its characteristic morphology in both hemispheres of the female adult fly brain (FAFB) 59 ( Figure 5 D). MooSEZ morphology implies dendritic regions mostly in the SEZ, and putative presynaptic projections in the lower lateral accessory lobe (LAL) 60 located posterior to the AL and extending lateroventrally—a major input region of MDNs.…”
Section: Resultsmentioning
confidence: 99%
“…Right (segment ID: 720575940622871283; nucleus coordinates: 110481, 71647, 5418) and left (segment ID: 720575940633628664; nucleus coordinates: 153740, 76085, 5035) MooSEZs were identified in the FAFB volume using FlyWire. 58 The natverse package was used to access, compare and visualize FlyEM hemibrain 57 and FlyWire 58 EM datasets and brain surface meshes for reference. 61 To identify and visualize MooSEZ and its postsynaptic cells in the FlyEM hemibrain dataset, the neuPrint+ web application (hemibrain:v1.2.1) “Simple connections” and "Find neurons" plugins 62 were used.…”
Section: Methodsmentioning
confidence: 99%
“…Future connectomic reconstructions encompassing the entire optic lobe will be necessary to unambiguously identify the putative cell types identified here. This can be in principle done by tracing in the full adult fly brain (FAFB) electron microscopy volume (Zheng et al, 2018) on the FlyWire website (Dorkenwald et al, 2021). An alternative approach is to use molecular tools to map connectivity among genetically defined cell types, such as trans-synaptic GFP reconstitution (GRASP) (Feinberg et al, 2008; Shearin et al, 2018), trans-Tango (Talay et al, 2017), and optogenetics (Simpson and Looger, 2018).…”
Section: Discussionmentioning
confidence: 99%